MiR-486-3p was downregulated at microRNA profiling of adrenals of multiple endocrine neoplasia type 1 mice, and inhibited human adrenocortical carcinoma cell lines - Li, Su-Chen; Monazzam, Azita; Razmara, Masoud; Chu, Xia; Stålberg, Peter; Skogseid, Britt (Scientific reports, 2021)
Adrenocortical carcinoma is a rare aggressive disease commonly recurring regardless of radical surgery. Although data on genomic alterations in malignant tumors are accumulating, knowledge of molecular events of importance for initiation of adrenocortical transformation is scarce. In an attempt to recognize early molecular alterations, we used adrenals from young multiple endocrine neoplasia type 1 conventional knock-out mice ( Men1 +/− ) closely mimicking the human MEN1 trait (i.e. transformation of pituitary, parathyroid, endocrine pancreatic, and adrenocortical cells). MicroRNA array and hierarchical clustering showed a distinct pattern. Twenty miRNAs were significantly upregulated and eleven were downregulated in Men1 +/− compared to wild type littermates. The latter included the known suppressor miRNA miR-486-3p, which was chosen for transfection in human adrenocortical carcinoma cell lines H295R and SW13. Cell growth decreased in miR-486-3p overexpressing clones and levels of the predicted target gene fatty acid synthase (FASN) and its downstream product, palmitic acid, were lowered. In conclusion, heterozygous inactivation of Men1 in adrenals results in distinct miRNA profile regulating expression of genes with impact on tumorigenesis, e.g. transcription, nucleic acid and lipid metabolism. Low levels of miR-486-3p in the early stages of transformation may contribute to proliferation by increasing FASN and thus fatty acid production. FASN as a potentially druggable target for treatment of the devastating disease adrenocortical carcinoma warrants further studies.